2020
DOI: 10.4025/actascianimsci.v43i1.48684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean meal replacement by slow-release urea on ruminal parameter, blood metabolites, and microbial protein synthesis in Zel ram

Abstract: The objective of this study was to determine the effect of soybean meal replacement by slow-release urea on feed intake, ruminal parameters, blood metabolites, dry matter, nutrients digestion, and microbial protein synthesis (MPS) in ram. Rams were used for four 21-day periods. The experimental design was a 4×4 Latin square design. The experiment has consisted of the following four rations: 1) basic diet with soybean meal as a protein source, 2) basic diet with soybean meal plus 0.5 % of DM slow-release urea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The pH is one of the important factors that affect the growth and reproduction of microscopic rumen organisms, especially the strains of fiber-decomposing organisms, and that eating concentrated feed works to reduce (pH), while eating coarse feed leads to its rise despite the high pH value in most of the treatments before feeding high that was obtained in the experiment is considered normal and that the average pH of the rumen environment is between (5.5-7.0) for the maximum bacterial growth of fiber digestion in the rumen [17,18] which promotes digestion and increases consumption. These came in agreement with [19][20][21] pH was not affected by increased SRU. While results differed with [22] that higher rumen pH increased by increased addition of slow-degrading urea and increased intake intake in sheep diets.…”
Section: Parameterssupporting
confidence: 89%
“…The pH is one of the important factors that affect the growth and reproduction of microscopic rumen organisms, especially the strains of fiber-decomposing organisms, and that eating concentrated feed works to reduce (pH), while eating coarse feed leads to its rise despite the high pH value in most of the treatments before feeding high that was obtained in the experiment is considered normal and that the average pH of the rumen environment is between (5.5-7.0) for the maximum bacterial growth of fiber digestion in the rumen [17,18] which promotes digestion and increases consumption. These came in agreement with [19][20][21] pH was not affected by increased SRU. While results differed with [22] that higher rumen pH increased by increased addition of slow-degrading urea and increased intake intake in sheep diets.…”
Section: Parameterssupporting
confidence: 89%
“…As for the AST enzyme, the statistical analysis results indicate that there are no significant differences in the concentration of the AST enzyme, as it ranged between (17.83-18.88 units/liter), which is an indication of the ewes' response to the addition of slow-release urea that improved the performance of blood enzymes as mentioned by some researchers in their studies [22,25]. However, it did not agree with the results of some studies [29,30], who indicated a significant decrease in the ALT enzyme while there were no significant differences for the AST enzyme.…”
Section: Resultsmentioning
confidence: 74%